2012
DOI: 10.4103/0971-4065.106029
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen antibody incompatible renal transplantation

Abstract: Anti-human leukocyte antigen (HLA) antibodies are recognized as an important problem in organ transplant recipients. This is because antibodies formed against a graft months or years after implantations are the major cause of late allograft failure, and also because protocols allow the transplantation of some grafts across pre-formed HLA antibodies. Advances in our understanding of anti-HLA antibody- mediated rejection (AMR) have occurred because of a better understanding of the histological findings during AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Human leukocyte antigen alloimmunization in candidates for renal transplantation is a reality [18] , [19] and knowledge of the incidence of sensitization to HLA antigens in the Brazilian population may be important for advances in renal transplantation and to minimize the waiting time for candidates [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen alloimmunization in candidates for renal transplantation is a reality [18] , [19] and knowledge of the incidence of sensitization to HLA antigens in the Brazilian population may be important for advances in renal transplantation and to minimize the waiting time for candidates [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The conventional complement-dependent lymphocytotoxicity (CDC) crossmatch is a traditional method for detection of human leukocyte antigen antibodies in patients awaiting kidney transplantation. 1,2 The CDC crossmatch (CDCXm) technique was performed to identify patients with a higher risk of developing hyperacute graft rejection (HAR) mediated by pre-formed donor-specific antibody (DSA). Such antibodies are formed as a result of previous exposure to HLA, generally through pregnancy, blood transfusion or previous transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the presence of anti-ABO antibody in the recipient is a risk for AMR, reducing antibody levels plays a key role in the success of the transplantation 10. Another study reported that high preoperative antibody titer did not have a significant effect on AMR, instead emphasizing the importance of preventing new antibody production after transplantation 11. Although the amount of acceptable pre-transplantation anti ABO antibody titer is not standardized for ABOi LDLT, desensitization protocols have been directed toward the elimination of anti-ABO antibody titers and suppression of B cell activity before and after transplantation.…”
Section: Discussionmentioning
confidence: 99%